Monomethylmercury behaviour in sediments collected from a mercury-contaminated lagoon - Ramalhosa, Elsa (2011)
Surface sediments and sediment cores were collected in a mercury (Hg)- contaminated lagoon, namely Largo do Laranjo – Ria de Aveiro, Portugal and analysed in order to establish the monomethylmercury (MeHg) behaviour in this kind of environment. In surface sediments, this compound was only detected in one place (13.2 ng g-1 (dry weight)). In this site, it was determined one of the lowest redox potentials (22 mV), indicative of oxic/anoxic conditions, which favours Hg methylation by enhancing the sulphate-reducing bacteria activity. However, the MeHg percentage obtained was low, namely less than 0.1% of the total Hg. This is probably due to Hg deposition with organic matter and iron oxyhydroxides, decreasing Hg availability to methylation. At the deeper layers, MeHg was also determined, reaching 46.4 ng g-1 (dry weight) and representing less than 0.1% of the total Hg. The higher MeHg percentages were observed near the surface, where Hg seems to be faster methylated as a result of the lower sulphide concencentrations that render bioavailable the inorganic Hg. At depth the low MeHg percentages obtained are due to the formation of HgS and to the adsorption of Hg to iron monosulphides.